Uji Efektivitas Konsentrasi Minyak Atsiri Sereh Dapur (Cymbopogon Citratus (DC.) Stapf) terhadap Pertumbuhan Jamur Aspergillus Sp. secara In Vitro - MARIA ULFA ELLA ELLA; KETUT SUMIARTHA SUMIARTHA; NI WAYAN SUNITI; I PUTU SUDIARTA; NYOMAN SEMADI ANTARA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2013)
ABSTRACT In Vitro Study of the effectiveness of Essential Oil Extracted from Lemongrass (Cymbopogon citratus) to Aspergillus Sp. Study on determining of the effectivenes of essential oil extracted from lemongrass (Cymbopogon citratus) in order to suppressing the growth of fruit rot fungi (Asoergillus sp.) and also to determining the minimum concentration that able to inhibit colony growth and spore formation of the Aspergillus sp. in vitro, was conducted in Laboratory of Plant Diseases from June into November 2012. The result showed that the fungi were isolated from rot fruit mango has similarities with the fungi Aspergillus sp. The characteristic of Aspergillus has cepted hyphae, growth appear colonies, conidiophores uncepted and stand up, the tip of conidiophore is swollen and produce vesicle form, the surface of vesicle is covered by fialid that usually simple and colored or colorless, fialid produced conidia which were form green, brown or black chain. Essential oil of lemongrass have an antifungal activity and it was found effective to inhibit growth of the fruit rot fungi Aspergillus sp. on PDA. The inhibition zone of the lemongrass essential oil against Aspergillus sp. were 85 mm which is include a very strong category. Effective concentration of essential oil of lemongrass to inhibit the growth of Aspergillus sp. are 0,6% - 1%. The persentase of inhibition in this concentration reached to 100%. On the other hand, the control treatment, 0,2%, and 0,4% concentration were 0%, 0%, and 28,53%, respectively. Minimum concentration which is capable to inhibit the formation of spores and growth of fungi colonies were 0,2% and 0,3% concentration. The compounds suspected as antifungal against Aspergillus sp. were ?-citral (geraniol) and ?-citral (neral). Keywords: Lemongrass (Cymbopogon citratus), essential oil, antifungi, Aspergillus sp.